Magneto-Chemically radiative micropolar nanofluid flow over an inclined stretching sheet with slip effects - Kumari, Pennelli Saila; Ibrahim, Shaik Mohammed (Journal of Naval Architecture and Marine Engineering, 2026)
This article conducts a detailed semi-analytical study on the steady flow of micropolar nanofluid over an inclined elongating sheet under multi-slip effects. This study examines the impacts of magnetic fields, heat source, chemical reaction, thermal radiation, and momentum, thermal, and concentration slip to model real-world systems for improved heat and mass transfer in key industrial applications. Similarity transformations convert the governing equations into nonlinear Ordinary Differential Equations (ODEs). The Homotopy Analysis Method (HAM) is used for numerical solutions. The results for the micropolar nanofluid's velocity, microrotation, temperature, concentration, friction factor, and mass and thermal transmission rates are presented pictorially and analyzed quantitatively. Findings reveal that enlarging thermophoresis, thermal source, radiation, and Brownian motion factors enhance the thermal distributions of the micropolar nanofluid flow. The validity of the results is confirmed through comparison with existing literature, demonstrating strong agreement. This study provides valuable insights into non-Newtonian fluid behavior and highlights the effectiveness of HAM-based numerical techniques in solving boundary layer problems. Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 129-144